Pengaruh Edukasi Pola Makan dan Senam terhadap Kadar Gula Darah Pada Penderita DM Tipe 2 - Selfi, Bela Febriana; Simbolon, Demsa; Kusdalinah, Kusdalinah (Politeknik Kesehatan Tanjungkarang, 2018)
The high prevalence of diabetes mellitus (DM) type 2 one risk factor is an unhealthy lifestyle, especially an unhealthy diet and lack of physical activity. Education followed by physical activity required to provide benefits to the body as a way of exercise can lower blood sugar. The recommended physical activity such as gymnastics, Gymnastics is aerobic physical exercise with a series of movements in a way to follow the rhythm of the music. The study aims to determine the effect of diet and exercise education on blood sugar levels in people with type 2 dm in Bengkulu City Puskesmas Lingkar Timur years 2018. This quasi-experimental research design.consists of 30 intervention and 30 control group. Gymnastics held 3 times a week for 1 week and education 1 time for 1 week, with an examination of the blood sugar levels of pretest and posttest. Data collection equipment consists of glucometers and bathroom scales and microtoice. The used statistical test Chi-Square test, t-dependent, and t-independent. The results of the study the characteristics of most women, age range 40-70 years intervention group and a control group 32-79 years, the average BMI in the intervention group is 24.21 m2 and 24.33 m2 in the control group, the intervention group showed that the levels of blood sugar before an average of 271.90 mg/dl, while the results of the blood sugar level after an average of 225.93 mg/dl. in the control group blood sugar levels before an average of 278.27 mg/dl whereas the blood sugar level results after an average of 285.67 mg/dl. Based on the statistical test that no educational influence diet and exercise on blood sugar levels in patients with type 2 dm p-value of 0.002. Expected to Type 2 diabetic patient's diet, increasing exercise and increased activity at home.